PENGARUH METODE ROLE PLAYING TERHADAP MINAT ANAK MENGIKUTI IBADAH SEKOLAH MINGGU USIA 8-12 TAHUN DI HURIA KRISTEN BATAK PROTESTAN PEANAJAGAR RESSORT PEANAJAGAR TARUTUNG TAHUN 2017 - Noverina Simangunsong (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, The purpose of this study was to determine the positive and significant effect of role playing method or role play against the interest of children following the Sunday school worship age 8-12 years in Huria Kristen Batak Protestan Peanajagar Ressort Peanajagar Tarutung. This research uses descriptive and inferential quantitative method. The population is all school children weeks of age 8-12 years inHuria Kristen Batak Protestan Peanajagar Ressort Peanajagar Tarutungwhich amounted to 121 people and the sample set 36 people By using random sampling technique. The data were collected with a closed questionnaire of 30 items. The results of data analysis showed that there is a positive and significant influence of role playing method on the interest of children following the Sunday school worship at the age of 8-12 years inHuria Kristen Batak Protestan Peanajagar Ressort Peanajagar Tarutungevidenced by the analysis of data as follows: 1) Test requirements analysis: a) test positive relationships obtained value rxy = 0.351 rtabel ( = 0,05, n = 36) = 0.329 Thus it is known that there is a positive relationship between variables X with the variable Y. b) Test a significant relationship obtained value t count = 2.044 ttable ( = 0,05, dk = n-2 = 34) = 2.042 thus there is a significant relationship between variables X with variable Y. 2) Test influence: a) Test the regression equation, obtained by regression equation. b) Test of regression coefficient of determination (r2) = 12%. 3) Hypothesis test using F test obtained Fcount Ftable is 6.678 1.62 thus H0 rejected and Ha accepted. Keywords: Role Playing Method, Child's Interest Following Sunday School Worship